The effect of Salvia leriifolia Benth. root extracts on lipid peroxidation level during global ischemic-reperfusion in rats - HR Sadeghnia; M Nassiri Asl; MH Haddadkhodaparast; H Hosseinzadeh (Institue of Medicinal Plants, ACECR, 2003)
The previous pathological data has revealed that Salvia leriifolia root extracts have a neuroprotective activity against cerebral ischemia, thus the effect of the root extracts on lipid peroxidation was evaluated using experimental global ischemic-reperfusion in the hippocampus of rats. Cerebral ischemia was induced by four-vessel-occlusion (4VO) for 20 min. The aqueous and ethanolic extracts (0.1, 0.2 and 0.4 g/kg), phenytoin, as positive control, (50 mg/kg) and normal saline (10 ml/kg) were administered intraperitoneally 15 min after the induction of ischemia. The malondialdehyde (MDA) was measured by the thiobarbituric acid (TBA) test. The MDA level was higher in the saline group than the sham group. The MDA levels were recovered significantly upon phenytoin and the extracts therapy in the hippocampus of ischemic rats. These results suggest that S. leriifolia root extracts may show a protective effect against lipid peroxidation in cerebral ischemia.